Analysis of military training of cadets of the Academy of the Interior Troops, Ministry of Internal Affairs, Ukraine, based on the air-field investigations as the reason for its adjustment - Poltorak S. Т.; Dovbnya, V. V.; Morozov О. О.; Pozhydayev А. О.; Sutyushev Т. А. (Honor and Law, 2019)
The analysis of military training of cadets of the Academy of the Interior Troops of Ukraine after the air-field investigations is given. Recommendations on adjustment the military training of cadets during their studies in the Academy are given.